THE YIELD OF WINTER WHEAT DEPENDING ON ITS FORE-CROP AND STUBBLE BIO-DESTRUCTOR - Panfilova, A. V.; Gamayunova, V. V.; Drobitko, A. V. (Scientific Progress & Innovations, 2019)
The article is devoted to increasing the yield of winter wheat by means of fore-crop choosing and using stubble bio-destructor by improving the nutrient soil regime and activating its microbiological activity. The experimental studies were conducted during 2011−2016 on the experimental field of Mykolaiiv National Agrarian University. The object of the research was Kolchuha winter wheat variety. The technology of its cultivation, except for the studied factors, was generally accepted as to the existing zonal recommendations for the southern steppe of Ukraine. The scheme of the experiment included the following variants: A factor – fore-crop: 1. spring barley; 2. pea. B factor – the treatment of crop residues: 1. water treatment as control; 2. treatment of stubble with bio-destructor (produced by the private enterprise “BTU-center”, Ukraine). Af-ter harvesting the spring barley and pea fore-crops the post-harvest residues of these crops were treated with the stubble bio-destructor (produced by the private enterprise “BTU-center”, Ukraine) at the dose of 2 liters of the bio-preparation and adding 3.0 kg of ammonium nitrate with the spray solution of 300 liters per 1 ha, after which the residues were disked by the heavy disk harrow BDT-7 to the depth of 10−12 cm. It should be noted that the gross content of basic nutrients in the plant residues depends significantly on the biological characteristics of crops and their yields. It was determined in our studies that on the average dur-ing the years of the research and according to the factor of treating post-harvest residues with the bio-destructor, after spring barley the soil contained 11.2 mg/kg of nitrates, 52.2 mg/kg of mobile phosphorus and 238.5 mg/kg of exchangeable potassium, which is respectively by 13.8; 11.8 and 14.2 % less than in the soil while cultivating winter wheat after pea. The experiments, conducted by us, showed that the number of nitrogen fixing agents in the soil increased under the action of treating crop residues of spring barley and pea with the stubble bio-destructor. Thus, in the variants without using the bio-preparation in the 0−10 cm experimental soil layer there were from 24.9 · 106 up to 32.5 · 106 pcs of nitrogen-fixing bacteria per 1 g of the soil, and in the layer of 10−20 cm there were from 21.8 ·106 up to 30.7 ·106 pcs / 1 g soil, which was re-spectively by 13.4 · 106−14.1 · 106 and 14.0 · 106−14.2 · 106 pcs / 1 g soil less or about 30.3 up to 35.0 and 31.6–39.1% less as compared with their number in the soil variants when using stubble bio-destructor. It should be noted that using pea as the fore-crop of winter wheat provides a slightly greater number of nitro-gen fixing agents as compared with spring barley in the soil layer of 0–10 cm by 7.6 up to 8.3 ·106 pcs / 1 g of soil or from 17.8 up to 23.4 %, and in the layer of 10–20 cm, the number of nitrogen fixing agents in-creased from 8.9 up to 9.1 · 106 pcs / 1 g of soil or 20.3 up to 29.0 % depending on the treatment of crop res-idues. As a result of the studies it was established that both during separate years of cultivation, and five years on the average, the grain yield of winter wheat was higher after its cultivation after pea. After spring barley it was from 1.19 up to 1.41 t/ha or 39.6–41.2 % lower depending on the variant of stubble bio-destructor application. The yield of winter wheat naturally grew in case of treating the fore-crop post-harvest residues with the bio-preparation. So, on average, during the years of the research, while cultivating winter wheat after spring barley and using the stubble bio-destructor the grain yield increased by 0.45 t/ha or 20.9 %, and after peas the grain yield increased by 0.67 t/ha or 18.8 % as compared with the variant of treating stubble only with water.